Search for the glueball content of hadrons in yp interactions at GlueX; Physical Review D; Vol. 94, iss. 3 - Gutsche Th. Thomas; Kuleshov S. V. Sergey Vasiljevich; Obukhovsky I. T. Igor Timofeevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2016, 2016)
Title screen